A Bioinspired Interface Design for Improving the Strength and Electrical Conductivity of Graphene‐Based Fibers. Issue 15 (27th February 2018) - Ma, Tao; Gao, Huai‐Ling; Cong, Huai‐Ping; Yao, Hong‐Bin; Wu, Liang; Yu, Zi‐You; Chen, Si‐Ming; Yu, Shu‐Hong
Abstract: Graphene‐based fibers (GBFs) are attractive for next‐generation wearable electronics due to their potentially high mechanical strength, superior flexibility, and excellent electrical and thermal conductivity. Many efforts have been devoted to improving these properties of GBFs in the past few years. However, fabricating GBFs with high strength and electrical conductivity simultaneously remains as a great challenge. Herein, inspired by nacre‐like multilevel structural design, an interface‐reinforced method is developed to improve both the mechanical property and electrical conductivity of the GBFs by introducing polydopamine‐derived N‐doped carbon species as resistance enhancers, binding agents, and conductive connection "bridges." Remarkably, both the tensile strength and electrical conductivity of the obtained GBFs are significantly improved to ≈724 MPa and ≈6.6 × 10 4 S m −1, respectively, demonstrating great superiority compared to previously reported similar GBFs. These outstanding integrated performances of the GBFs provide it with great application potential in the fields of flexible and wearable microdevices such as sensors, actuators, supercapacitors, and batteries. Abstract : Both the mechanical properties and electrical conductivity of graphene‐based fibers (GBFs) are improved by a novel interface‐reinforced method by introducing polydopamine (PDA)‐derived N‐doped carbon species as resistance enhancers, binding agents, and conductive connection "bridges". Ultimately, both the tensile strength and electrical conductivity of the obtained GBFs are significantly improved.